Projeto e simulação de rede MPLS - Freitas, Mauricio Dada Fonseca de (2013)
This monograph aims at synthesizing the basic theory around the MPLS (MultiProtocol Label Switching) technology. It serves as a first contact with the technology, requiring some basic prior knowledge in WAN (Wide Area Networks) concepts. The project comprises the explanation of the main concepts and those are illustrated by a simulation of the network. The simulation begins with choosing a compatible equipment, defining the topology and connections, distributing IP addresses, configuring all protocols, meticulously analyzing the forwarding tables and a introducing some basic notion of troubleshooting.